2008
DOI: 10.4028/www.scientific.net/amr.47-50.258
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Responsive Shape-Memory Polymer Driven by Forming Hydrogen Bonding

Abstract: Recently, there is interest in triggering shape recovery of shape-memory polymers(SMPs) by novel non-external heating. In this paper, many hard works have been carried out to make SMP induced by solution. The main challenge in the development of such polymer systems is the conversion of solution-induced effects at the molecular level to macroscopic movement of working pieces. This paper presents a systematic study on the effects of solution on the glass transition temperature (Tg). The results reveal that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…As shown in Figure 6, E' M A N U S C R I P T [39][40][41][42]. Moreover, the changes in the moduli of present feather rachis can be further diminished by the porous structure of medullary foam.…”
Section: Water Effect and Mechanismsmentioning
confidence: 92%
“…As shown in Figure 6, E' M A N U S C R I P T [39][40][41][42]. Moreover, the changes in the moduli of present feather rachis can be further diminished by the porous structure of medullary foam.…”
Section: Water Effect and Mechanismsmentioning
confidence: 92%
“…It is observed that the T g sharply decreases with water absorption and levels off with the W value of 0.388 g Á g À1 . Water penetrates into the deformed samples and acts like a plasticizer to increase the mobility of the polymer chains, [33,48] which brings about the change in entropic elastic properties of the polymer chains. The free shape recovery of the samples is enabled even at RT (Figure 1, group A).…”
Section: Effect Of Water Content On the Thermal Mechanical Propertiesmentioning
confidence: 99%
“…[27,28] Considering the extensive applications of PVA to medical devices, the promising SME of SM-PVA, and especially the unique properties of MWs, [29][30][31] we speculate that MW induced SM-PVA will have great potential for applications, in particular, in those fields that direct contact between the heating source and the heated material is not allowed and remote-controlled actuators are required, such as MW responsive sensors, vascular stents, and other medical devices. [8,32,33] Experimental Section…”
Section: Introductionmentioning
confidence: 99%
“…Solution-responsive SMPs present a significant decrease in the modulus during phase transition [45]. Water-driven actuation of SMPs was first discussed in 2005 by Huang [46].…”
Section: Solution-responsive Smpsmentioning
confidence: 99%